2017
DOI: 10.1097/ogx.0000000000000423
|View full text |Cite
|
Sign up to set email alerts
|

Actinomyces in Pregnancy: A Review of the Literature

Abstract: After completing this activity, the learner should be better able to identify the areas of the body where infections occur and how the infections typically occur, identify the pathophysiologic changes that occur during pregnancy that might lead to an infection and how that infection may affect pregnancy outcomes, and describe the treatment for mild and severe infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…The metabolic ability of Actinomyces may be due to the decomposition and recovery of organic compounds in the human gastrointestinal system [ 50 ]. In rare conditions, chorioamnionitis and preterm delivery can be complicated by Actinomyces infection [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…The metabolic ability of Actinomyces may be due to the decomposition and recovery of organic compounds in the human gastrointestinal system [ 50 ]. In rare conditions, chorioamnionitis and preterm delivery can be complicated by Actinomyces infection [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…A. meyeri has also been found to be an uncommon source of obstetrical infection [ 8 ]. These cases are described in a recent literature review published in 2017, which found 17 cases of obstetric related Actinomyces infections.…”
Section: Discussionmentioning
confidence: 99%
“…These cases are described in a recent literature review published in 2017, which found 17 cases of obstetric related Actinomyces infections. A particular species of Actinomyces was identified in only five of these cases, with the identified species including A. israelii , A. neuii , and A. meyeri [ 8 ]. Additionally, a single report describes a case of fatal sepsis related to pyomyoma; however, this infection was not following any surgical intervention or instrumentation of the uterus.…”
Section: Discussionmentioning
confidence: 99%
“…It can result in infection after a break in the normal defenses of the mucosa [128]. Actinomycosis is found in pregnancy very rarely, but according to a recent review, if it occurs, it is mainly associated with preterm deliveries [129].…”
Section: Actinomycesmentioning
confidence: 99%